Rwanda : Second and Third Reviews Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Request for Waiver of Performance Criteria, and Request for Additional Interim Assistance Under the Enhanced HIPC Initiative. (IMF Staff Country Reports; Country Report ;, 2004)
Rwanda's Second and Third Reviews under the Poverty Reduction and Growth Facility, and request for Waiver of Performance Criteria are discussed. After an extended period characterized by a strong expansion of economic activity, real GDP growth is estimated by IMF staff to have slowed to 0.9 percent in 2003. On the structural side, performance criteria on the revision of the tax law and preparation of the financial instructions for more effective expenditure management have been met.